Allometric equations to estimate aboveground and belowground biomass of Pinus patula Schiede ex Schltdl. & Cham - Arcelio Martínez-Domínguez; Faustino Ruiz-Aquino; Wenceslao Santiago-García; Pablo Antúnez; Miguel Ángel López-López; Cesar Valenzuela-Encinas; Rossy Feria-Reyes (Forest Science and Technology, 2020)
The estimation of tree biomass serves as a parameter of forest productivity; in addition, it is a method to estimate carbon fixation and storage. Studies on total biomass that include the belowground component for the Pinus genus are scarce in Mexico due to the difficulty and high costs for its quantification. In this study, allometric models were fitted to estimate the total biomass of Pinus patula Schiede ex Schltdl. & Cham., from the pine-oak forest of Ixtlán de Juárez, Oaxaca, for which a destructive analysis was made of 25 trees distributed in five diameter classes, classifying the biomass by components (root, stem, branches and foliage). With the component biomass data, different models were fitted by nonlinear regression techniques, using the diameter at breast height (D, cm) and the total height (TH, m) as independent variables. The model with the best fit was an exponential type In this study, it was observed that the studied species stores 22.62% of the biomass in the root, 69.61% in the stem, 5.67% in the branches and 2.11%, in the foliage. The models proposed in this study allow the estimation of total biomass and by structural component independently and additively. Its use is recommended in trees of P. patula, in the range of 5 to 25 cm of diameter at breast height, in forests with similar growing conditions.